PARTIAL REPLACEMENT OF FINE AGGREGATE WITH SHREDDED PLASTIC - Prof.Y.B. Survase1, Dr. M. G. Dheshmukh2, Prof. Sonali S. Patil3, Asha K. Shinde3, Shaheen J. Shaikh3, Sony D. Kotwal3, Vrushali S. Shivharan3, Pratiksha D. Surwase3. (International Journal of Innovations in Engineering Research and Technology, 2022)
The concrete is the second largest material using on earth after water. In India, approximately 400 million metric cube concrete is being used every year and is increasing day by day. This increase in demand will create disturbance in proportion between availability and need of material. Hence an alternative material is required to vanishing this disturbance. In this paper studies conducted on utility of waste shredded plastic material used in the concrete. Moreover, this paper will focus toward the change in various properties of concrete when partially replacing with shredded plastic. Concrete with 0.5%, 1.0%, 2%, 4% and 6 % shredded plastic is prepared. Specific gravity, fineness, setting time, sieve analysis, fineness modulus tests on cement, coarse and fine aggregates are performed in this study. As per IS 10262-2009 mix design code, Mix design is done. Cubes and beams are cast for M20 grade concrete with and without shredded plastics and tests on concrete are conducted. The standard mechanical properties of concrete like compressive strength, flexure and strength are tested and compared with the results of standard specimen.